Unfolding the leaf economics spectrum for wheat : Trait analysis and genomic associations across cultivars - Yibo Li; Fulu Tao; Yuanfeng Hao; Jingyang Tong; Yonggui Xiao; Zhonghu He; Reynolds, Matthew P. (Elsevier, 2024)
The leaf economics spectrum (LES) is an ecophysiological concept that describes the trade-offs between leaf structural and physiological traits. It has been extensively studied across various scales. However, the coordination hypothesis has rarely been tested at the intraspecific scale, especially in crops, for understanding yield increases or predicting evolutionary trajectories. Here, we first tested the relationships among leaf traits and examined the genetic coordination among 209 wheat genotypes. Compared to non-crop grass species, wheat is a fast-growing species, and tends to have a higher value of photosynthetic rate, leaf nitrogen concentration and leaf respiration rate at a given leaf mass per area, although it does align with the predicted direction of the “fast-slow” spectrum. We conducted a principal component analysis (PCA) to compare different traits within wheat. The first axis from PCA (ranging from slow to fast of plant economic investment) is significantly positively associated with the agronomic traits, especially grain yield (R2=0.11, P<0.001). Partially independent changes in leaf nitrogen content and leaf mass per area may allow crops to maximize photosynthetic rates without sacrificing leaf lifespan. The results reveal that some loci are simultaneously associated with different traits, which may be the genetic basis for the formation of trait-trait relationships. The current study deepens the understanding of LES traits in wheat at the intraspecific and genetic levels, supporting the trait-based adaptation strategies to improve wheat productivity and resource-use efficiency.